Dark Energy Survey Year 3 Results: Deep Field optical + near-infrared images and catalogue. Issue 3 (27th October 2021) - Hartley, W G; Choi, A; Amon, A; Gruendl, R A; Sheldon, E; Harrison, I; Bernstein, G M; Sevilla-Noarbe, I; Yanny, B; Eckert, K; Diehl, H T; Alarcon, A; et al.
ABSTRACT: We describe the Dark Energy Survey (DES) Deep Fields, a set of images and associated multiwavelength catalogue ( ugrizJHKs ) built from Dark Energy Camera (DECam) and Visible and Infrared Survey Telescope for Astronomy (VISTA) data. The DES Deep Fields comprise 11 fields (10 DES supernova fields plus COSMOS), with a total area of ∼30 sq. deg. in ugriz bands and reaching a maximum i -band depth of 26.75 (AB, 10σ, 2 arcsec). We present a catalogue for the DES 3-yr cosmology analysis of those four fields with full 8-band coverage, totalling 5.88 sq. deg. after masking. Numbering 2.8 million objects (1.6 million post-masking), our catalogue is drawn from images coadded to consistent depths of r  = 25.7, i  = 25, and z  = 24.3 mag. We use a new model-fitting code, built upon established methods, to deblend sources and ensure consistent colours across the u -band to Ks -band wavelength range. We further detail the tight control we maintain over the point-spread function modelling required for the model fitting, astrometry and consistency of photometry between the four fields. The catalogue allows us to perform a careful star–galaxy separation and produces excellent photometric redshift performance (NMAD = 0.023 at i < 23). The Deep-Fields catalogue will be made available as part of the cosmology data products release, following the completion of the DES 3-yr weak lensing and galaxy clustering cosmology work.